Efisiensi Teknis Perkebunan Kelapa Sawit Rakyat - Simatupang, Jones; Simatupang, Aditia Erick Cantona; Nababan, Manaor Bismar Posman (Hasanuddin University, 2025)
This study aims to determine the technical efficiency value of smallholder oil palm plantations in Bandar Pasir Mandoge District and to identify the socio-economic factors that influence the technical efficiency of these plantations. The method of determining the area was purposive, specifically in Huta Padang Village and Huta Bagasan Village, Bandar Pasir Mandoge District, Asahan Regency. This sampling method employs simple random sampling. This research method employs the Data Envelopment Analysis (DEA) approach to estimate technical efficiency, and also utilises Tobit regression to evaluate the factors that influence efficiency. The results of this study are: (1) The technical efficiency value of smallholder oil palm plantations in Bandar Pasir Mandoge District based on the CRS assumption is 0.929, the technical efficiency value based on the VRS assumption is 0.941, the technical efficiency value SE is 0.987 which means that from the three variables, farmers are still not said to be efficient. The dominant production scale is in the IRS. The average input reduction is based on the CRS assumption (2) Socio-economic factors that significantly influence the technical efficiency of smallholder oil palm plantations in Bandar Pasir Mandoge District are education, farming experience and application of organic fertiliser. Socio-economic factors that have an insignificant influence on the technical efficiency of smallholder oil palm plantations in Bandar Pasir Mandoge District include gender, number of family members, distance to the PKS, and access to credit.